PANDANGAN ‘URF TERHADAP PROSESI ADAT KARIA PADA MASYARAKAT MUNA DI KELURAHAN LAIWORU KECAMATAN BATALAIWORU KABUPATEN MUNA - Mohasa, Muhammad Fajri; Musyfikah Ilyas; Abdul Syatar (Universitas Islam Negeri Alauddin Makassar, 2023)
Abstract Karia custom is a custom carried out by the Muna community who are Muslim. The main problem of this research is the 'urf' view of the traditional karia procession in the Muna community in Laiworu Village, Batalaiworu District, Muna Regency with sub problems, namely:1. How is the practice of performing traditional caries in the Muna community in Laiworu Village, Batalaiworu District, Muna Regency? And 2. What is 'urf's view on the practice of performing traditional caries in the Muna community in Laiworu Village, Batalaiworu District, Muna Regency? This type of research is a field research (field research), which is descriptive qualitative. The research approach used is the 'Urf approach and the Socio-cultural approach. The results of this study indicate that: Karia is one of the customs of the Muna tribe that has been passed down from generation to generation. And the karia custom is a custom that includes 'urf sahih, meaning that the karia custom is a custom that is allowed in Islam. The implication of this research is that for the Muna Regency Government, adat karia as cultural heritage values ​​should be preserved, especially noble values ​​in the implementation of adat karia to shape women's personalities in living married life. Keywords: karia custom, Islamic law, ‘urf